Immunoregulatory Effect Of Ethanolic Extract Propolis (Eep) From Geniotrigona Thoracica Sp. On The Formation Of Thp-1 Derived Macrophage Foam Cells - Suib, Muhammad Syamil Mohd (2018)
Propolis is a complex resinous substances collected by bees from buds and exudates of plants that has been reported to demonstrate various therapeutic potential. The usage of natural product such as propolis has been used for treatment of various chronic diseases which includes atherosclerosis. Atherosclerosis is a chronic inflammatory disease involving the formation of monocyte derived macrophage foam cells in arteries, which play a major role in atherogenesis. Studies showed that propolis produced by honeybees may inhibit atherosclerosis but there is no studies that have been performed using propolis produced by Indo-Malayan stingless bees. Hence, this study was carried out to investigate the effect of propolis from Geniotrigona thoracica species on the formation of foam cells. Propolis from three different colonies of Geniotrigona thoracica species were extracted using 80% ethanol. The volatile and non-volatile compounds present in ethanolic extract of propolis (EEP) were analysed via GC-MS and HPLC analysis. The optimal concentration of EEP (0-200 μg/ml) to treat THP-1 derived macrophages was determined via in vitro cell viability assay by using PrestoBlue®. THP-1 cells were differentiated to THP-1 derived macrophages using 100 ng/ml of PMA for 72 hours. Then, THP-1 derived macrophages were treated with 80 μg/ml of oxidized LDL (oxLDL) and 20 μg/ml of EEP for 6, 24 and 48 hours. The morphological appearance of foam cells was determined by Oil Red O staining while the amount of cholesteryl ester (CE) present in the foam cells were quantified by using Cholestryl Ester Quantitation Assay Kit. Lastly, the level of inflammatory cytokine secretions, TNF-α and IL-1β secreted by the treated cells were measured by ELISA. Propolis extract of Geniotrigona thoracica sp. was found to have high abundance of triterpenoids and the presence of caffeic acid, p-Coumaric acid and quercetin compounds via GC-MS and HPLC analysis respectively. EEP from Colony 2 was selected to be used in this study as it has higher abundance of bioactive compounds. The